Accumulation of organochlorine pesticides in fat tissue of wild Nile crocodiles (Crocodylus niloticus) from iSimangaliso Wetland Park, South Africa. (March 2018) - Buah-Kwofie, Archibold; Humphries, Marc S.; Combrink, Xander; Myburgh, Jan G.
Abstract: Nile crocodiles ( Crocodylus niloticus ) are important apex predators in many tropical and subtropical aquatic habitats throughout much of sub-Saharan Africa. In South Africa, large crocodile populations inhabit lakes and wetlands that are impacted by organochlorine pesticides (OCPs). Despite the continued use of these compounds and their potential adverse effects on key wildlife populations in southern Africa, limited ecotoxicoloigcal data exist. In this study, we examined the accumulation of OCPs in fat tissues of live, wild Nile crocodiles from iSimangaliso Wetland Park, a region of significant biological importance. All samples (n = 15) contained multiple contaminants in highly elevated concentrations, with total residue burdens varying between 3600 and 8000 ng g −1 ww. DDT and its metabolites were the dominant compounds detected in most samples, with ∑DDT concentrations ranging between 520 and 3100 ng g −1 ww. Elevated levels of other OCPs were also detected, including lindane (67–410 ng g −1 ww), aldrin (150–620 ng g −1 ww) and heptachlor (170–860 ng g −1 ww). Our findings show that crocodiles are exposed to OCPs throughout their range within iSimangaliso Wetland Park and contain some of the highest concentrations ever recorded in crocodilian tissue. Results indicate the need for a greater understanding of the impacts of OCP exposure and toxicological responses in crocodiles from iSimangaliso, and in Nile crocodile populations in general. The novel surgical technique described in this study provides an effective method for assessing relationships between contaminant body burdens and their potential reproductive and developmental consequences in crocodilians. Highlights: First report on OCP concentrations in fat tissues from Nile crocodiles. Analyses reveal highly elevated DDT contaminant burdens. We describe a novel surgical technique for the analysis of fat from crocodilians. We highlight ecotoxicological concerns and the need to better understand risks.